The Spectre of Capital: Idea and Reality - Arthur, Christopher J. (Brill, 2022)
What is money? What is capital? The Spectre of Capital tackles such fundamental questions at a deep philosophical level. It argues that the modern world is ruled by a 'spectre', the spectre of capital. This insight is rooted in an original combination of the ideas of Marx and Hegel. It presents the most sophisticated argument to date for 'the homology thesis', namely that the order of Hegel's logical categories, and that of the social forms addressed by Marx's Capital, share the same architectonic. The systematic-dialectical presentation shows how capital becomes a self-sustaining power.